Musealisation of the archaeological site of Praça Nova at São Jorge Castle, Lisbon (2008–2010) - Sequeira, M. (Flashback: Carrilho da Graça, 2022)
An extensive archaeological campaign that began in 1986 in the Praça Nova at São Jorge Castle, Lisbon, uncovered various traces of the area’s occupation through successive periods — an Iron Age settlement, medieval Islamic dwellings and a 15th-century palace. While the most relevant artifacts were removed and exhibited in the castle’s museological centre, the project for the musealisation of the archaeological site was drawn up with the aim of making known and conserving the excavation space. To protect what remained of the two Islamic houses, Carrilho da Graça decided to make a conjectural, abstract and scenographic reconstitution of these buildings resembling a life-sized model — spatializing the ruin, that is, protecting the archaeological site while revealing its hypothetical original configuration. As well as being the starting point for a line of research into interventions at the sites of ruins, this project constitutes a manifesto, as the spatiality of these 11th-century houses does not seem to difer much from that of other courtyard houses that he himself had previously designed and would continue to design into the future